Reviewers 2022 - Revista del Hospital Italiano de Buenos Aires (Revista del Hospital Italiano de Buenos Aires, 2023)
The following list includes the professionals who reviewed the papers submitted to the Revista del Hospital Italiano de Buenos Aires during the year 2022. The task performed altruistically by the peer reviewers is crucial for our publication to fulfill its commitment to disseminate scientific knowledge with high quality standards. For this reason, the Editorial Board is deeply grateful to all of them for their dedication, responsibility and intellectual honesty.